Osteopontin Expression in the Brain Triggers Localized Inflammation and Cell Death When Immune Cells Are Activated by Pertussis Toxin - Maria Cecilia Garibaldi Marcondes; Ryan Ojakian; Nikki Bortell; Claudia Flynn; Bruno Conti; Howard S. Fox (Mediators of Inflammation)
Upregulation of osteopontin (OPN) is a characteristic of central nervous system pathologies. However, the role of OPN in inflammation is still controversial, since it can both prevent cell death and induce the migration of potentially damaging inflammatory cells. To understand the role of OPN in inflammation and cell survival, we expressed OPN, utilizing an adenoviral vector, in the caudoputamen of mice deficient in OPN, using beta-galactosidase- (β-gal-) expressing vector as control. The tissue pathology and the expression of proinflammatory genes were compared in both treatments. Interestingly, inflammatory infiltrate was only found when the OPN-vector was combined with a peripheral treatment with pertussis toxin (Ptx), which activated peripheral cells to express the OPN receptor CD44v6. Relative to β-gal, OPN increased the levels of inflammatory markers, including IL13Rα1, CXCR3, and CD40L. In Ptx-treated OPN KOs, apoptotic TUNEL+ cells surrounding the OPN expression site increased, compared to β-gal. Together, these results show that local OPN expression combined with a peripheral inflammatory stimulus, such as Ptx, may be implicated in the development of brain inflammation and induction of cell death, by driving a molecular pattern characteristic of cytotoxicity. These are characteristics of inflammatory pathologies of the CNS in which OPN upregulation is a hallmark.